Experimental Investigation on Anti-detachment Strengthening Technology for Exterior Wall Ceramic Claddings of Existing Buildings - Pan Jinjing; Liu Jing; Wang Xuan; Zhang Zihua; Yang Feng; Xu Shunbi; Zhang Yaqi; Lin Hongfei; Chen Chao; Xuan Yang (E3S Web of Conferences, 2023)
To study the effect of anti-detachment strengthening technology for ceramic claddings, several experiments were performed to obtain the failure mode and bonding strength of the strengthened hollow ceramic claddings system exterior wall, and were compared with the unreinforced system. The results indicated that using a transparent polymer waterproof coating layer as a covering material in strengthening technology could effectively improve the failure mode and adhesive strength of the hollow ceramic cladding system on the exterior wall.